Moonwalking with Einstein: The Art and Science of Remembering Everything - Joshua Foer (Penguin Books, 2011)
Why don't some waiters need to write down orders? How are the best violinists able to memorize a new score after playing it only once? Why can some people commit entire books to memory - while a few can only remember their most recent thought? To answer these questions, Joshua Foer spent a year talking to memory experts and neuroscientists, savants and amnesiacs, chess masters and historians of memory. He learnt the principles of memory techniques, from Cicero to modern day 'memory palaces', and even undertook intense training under a Grand Master to become a US Memory Champion. Looking at everything from why London cabbies' brains develop differently to how Apache Indians remember landmarks, Foer discovers the mechanics of memory and reveals how the brain can be exercised like any other muscle. In fact, he shows, with the right training, we can all achieve mastery of our memory. Intelligent, entertaining and with a cast of unforgettable characters, Moonwalking with Einstein revives the long-lost tradition of memory training to show us the potential of our minds.